Student engagement with course content and peers in synchronous online courses discussions - Truhlar, Allison M; Williams, Kimberly M; Walter, M Todd (Online Learning, 2019)
As higher education institutions in United States offer online courses to growing audiences, there is increasing desire to understand how best to engage students with both course content and their peers. This case study examines the effects of assigning chat roles and facilitating self and group reflection on student-content and student-student interaction outcomes in four synchronous chats conducted in an online introductory-level sustainability course. We also considered what occurred within group reflections to inform how they are structured in the future. We found that assigning roles increased the proportion of critical student-student interactions. Self-reflections had no effect on either interaction type. Groups completing group reflections had a greater proportion of critical student-content interactions in the third chat and critical student-student interactions in the fourth chat than the groups that did not complete the group reflections. Based on our results, we plan to keep roles and group reflections going forward, and eliminate self-reflections. Furthermore, to increase the effectiveness of the group reflections, we propose some ideas to increase student ability to convert their ideas into change during subsequent chats.